Pengembangan Media Pembelajaran Berbentuk Komik pada Pembelajaran Matematika Materi Pecahan Kelas V Sekolah Dasar - Adena Nurasiah Siregar (Al Yazidiy Jurnal Sosial Humaniora dan Pendidikan, 2023)
Many students consider math lessons trivial and not exciting, because, some teachers still use learning media that are not interactive and seem conventional such as blackboards. This makes students bored, passive and difficult to learn, especially learning fractions. Thus, this study intends to create a good fraction math learning media such as comics and in line with student development. This study uses the Research & Development (R&D) method with the ADDIE model. The target of this study was grade V students. The data collection technique uses observation and questionnaire. In line with the results of the validity of media experts can achieve 88%, in line with the responses of teachers and students can achieve 85%. Thus, the resulting product gets a decent achievement worthy of use for learning media mathematics grade V elementary school and effective use.